2021
DOI: 10.3390/molecules26133810
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Study of Biomarkers from Novichok-Inhibited Butyrylcholinesterase in Human Plasma

Abstract: To identify biomarkers of ethyl (1-(diethylamino)ethylidene)phosphoramidofluoridate (A234)- or methyl (1-(diethylamino)ethylidene)phosphoramidofluoridate (A232)-inhibited butyrylcholinesterase (BChE), we investigated nonapeptide adducts containing the active site serine, which plays a key role in enzyme activity, using LC-MS/HRMS. Biomarkers were acquired as expected, and they exhibited a significant amount of fragment ions from the inhibiting agent itself, in contrast to the MS2 spectra of conventional nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…For example, three phosphoryl-containing features were found to have a significant association with AChE/BChE inhibition in this study, e.g., “bond: PO_phosphorus_oxo” for AChE inhibition ( P value = 3.73 × 10 –15 ), “bond: PO_phosphate_dithio” for selective AChE inhibition ( P value = 9.14 × 10 –5 ), and “bond: PO_phosphonate_aliphatic_ester” for BChE inhibition ( P value = 2.14 × 10 –2 ) (Table and Table S4). Consistent with these findings, organophosphate nerve agents containing a phosphoryl (PO bond) group have been reported to disrupt cholinergic neurotransmission by irreversibly inhibiting AChE and BChE activity. , The feature “ring:hetero_[6_6_6]_N_S_phenothiazine” was found significant for BChE selectivity ( P value = 5.00 × 10 –4 ) in this study (Tables and S4). Consistent with this finding, there have been cases in the literature that the phenothiazine core was the basis for selective inhibition of BChE. For example, ethopropazine, which contains the “ring:hetero_[6_6_6]_N_S_phenothiazine” feature, is a highly selective inhibitor of BChE over AChE (∼1000-fold selectivity) …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…For example, three phosphoryl-containing features were found to have a significant association with AChE/BChE inhibition in this study, e.g., “bond: PO_phosphorus_oxo” for AChE inhibition ( P value = 3.73 × 10 –15 ), “bond: PO_phosphate_dithio” for selective AChE inhibition ( P value = 9.14 × 10 –5 ), and “bond: PO_phosphonate_aliphatic_ester” for BChE inhibition ( P value = 2.14 × 10 –2 ) (Table and Table S4). Consistent with these findings, organophosphate nerve agents containing a phosphoryl (PO bond) group have been reported to disrupt cholinergic neurotransmission by irreversibly inhibiting AChE and BChE activity. , The feature “ring:hetero_[6_6_6]_N_S_phenothiazine” was found significant for BChE selectivity ( P value = 5.00 × 10 –4 ) in this study (Tables and S4). Consistent with this finding, there have been cases in the literature that the phenothiazine core was the basis for selective inhibition of BChE. For example, ethopropazine, which contains the “ring:hetero_[6_6_6]_N_S_phenothiazine” feature, is a highly selective inhibitor of BChE over AChE (∼1000-fold selectivity) …”
Section: Discussionsupporting
confidence: 86%
“…Consistent with these findings, organophosphate nerve agents containing a phosphoryl (P�O bond) group have been reported to disrupt cholinergic neurotransmission by irreversibly inhibiting AChE and BChE activity. 13,14 The feature "ring:hetero_[6_6_6] _N_S_phenothiazine" was found significant for BChE selectivity (P value = 5.00 × 10 −4 ) in this study (Tables 1 and S4). Consistent with this finding, there have been cases in the literature that the phenothiazine core was the basis for selective inhibition of BChE.…”
Section: ■ Discussion and Conclusionsupporting
confidence: 49%
See 1 more Smart Citation
“…In the meantime, theoretical and mass spectrometry studies have appeared that ascertain the structures shown in Fig. 1 (Bhakkoa et al 2019 ; Lee et al 2021 ; Jeong et al 2021 ).…”
mentioning
confidence: 99%
“…Rapid advances in mass spectrometry to acquire high-quality data with greater resolution will enable analysis of protein and DNA adducts of xenobiotics including chemical warfare agents. In this context, Jeong et al ( 2021 ) investigated nonapeptide adducts of Novichok A 232 an A 234 to the active serine site of butyrylcholine esterase, which plays a key role in enzyme activity, using LC–MS/HRMS. Biomarkers exhibited a significant amount of fragment ions from the inhibiting agent.…”
mentioning
confidence: 99%